Study on Seismic Dynamic Response of Deep-Buried Tunnel Based on Tectonic Stress - Junjie He; Song Hu; Yonggang Guo (Advances in Materials Science and Engineering)
The southeast region of Tibet in China is prone to earthquakes at high seismic levels. Since the construction of tunnels in this region faces a seismic hazard, it is necessary to explore the seismic responses of related construction areas there. In this study, a high-precision finite model of a mountain in a construction area was established based on a deep-buried tunnel in Southeast Tibet. Core specimens were obtained through on-site drilling, with the initial tectonic stress in the tunnel area measured by using the hydraulic fracturing method. Dynamic mechanical parameters of the rocks were acquired through in-situ testing. Moreover, indoor tests were conducted to obtain the physical and mechanical properties of the rocks. The tectonic stress, identified through multiple linear regression inversions, was used as the initial condition for dynamic calculation. The dynamic responses of the tunnel-engineering area under seismic action were calculated, followed by an analysis of the dynamic response characteristics. In addition to dramatic fluctuations in mountain topography, complex dynamic response characteristics of the mountain structure in earthquake environments were also revealed. Although the displacement time-history curve of each observation point displayed a consistent fluctuating pattern, the dynamic displacement extremes in different areas of the mountain varied significantly when the time arrived for their appearance. A maximum dynamic displacement of 0.53 m was observed at the observation point with the highest elevation (5,265.8 m). The acceleration amplification effect inside the mountain body was obvious, with the acceleration increasing as the elevation rose. The time for the occurrence of PGA (acceleration extreme) of each observation point in different directions differed substantially. The extreme value of dynamic stress along the tunnel axis conformed to the distribution pattern of the initial tectonic stress. Compared to the initial tectonic stress, the dynamic stress increased significantly at all observation points along the tunnel axis, with the dynamic stress increasing at a larger rate in the areas at a greater buried depth. Horizontal dynamic stress Sx at the maximum buried depth and Sy increased to 13.86 MPa and 10.32 MPa, respectively, and vertical dynamic stress Sz increased to 4.30 MPa. Variations in horizontal stress became more apparent as the elevation rose, in contrast to weakened variations in vertical stress as the elevation dropped. This study aims to explore the dynamic responses of mountains and the variation law of tectonic stress in deep-buried tunnels in earthquake environments in Tibet through qualitative analysis. The results revealed drastic changes in acceleration, dynamic displacement, and ground stress in the tunnel-engineering area. It is hoped that the contents of the study will contribute to the prevention and control of seismic geological hazards in the tunnel-engineering region and render technical support for the design and construction of similar projects in this region.